Hypovolemic Shock in pregnancy secondary to DKA with superimposed Sepsis: Dilemmas and clinical patient safety pathways are critical components to prevent Maternal and Neonatal mortality: A Case Report - Dogra, Sandeepika; Pandya, Sunil T; Madapu, Manokanth; Gupta, Kanika (Journal of Neonatal Surgery, 2025)
We want to report a case of a 26-year-old primigravida at 31 weeks with type 1 Diabetes Mellitus (BMI 31) who was admitted for persistent vomiting and fever and diagnosed with Diabetic Ketoacidosis (DKA). In the ICU, she developed a right breast abscess, worsening metabolic acidosis, and septic shock, requiring mechanical ventilation and inotropes. The patient landed in Hypernatremia, making the multidisciplinary team switch from normal saline to Plasmalyte. Due to hemodynamic instability, a Category I cesarean section under general anesthesia was performed, delivering a 1.64 kg baby girl (APGAR 5/6/6). Post-delivery, she received intensive care, and the abscess was drained. Quick management and decisive actions, including reconsidering fluid therapy and timely C-section, were crucial to the rapid improvement, averting double jeopardy and imminent maternal and neonatal morbidity and mortality. Both mother and baby gradually recovered in the ICU, bonding via.